A case of central venous catheter-related Candida parapsilosis fungemia evolved to disseminated infection in a neutropenic patient with blast crisis of chronic myeloid leukemia. - Elena Amabile; Matteo Totaro; Luca Cappelli; Clara Minotti; Alessandra Micozzi (Mediterranean Journal of Hematology and Infectious Diseases)
Central venous catheter-related infections are of particular importance in onco-hematological patients. Candida parapsilosis is generally reported as a mild pathogen, however it is able to effectively colonize intravascular devices and potentially give rise to sustained fungemias. Here we report a case of invasive, potentially lethal C. parapsilosis disseminated infection in a neutropenic patient affected by chronic myeloid leukemia with blast crisis. We underline the importance of removing the central venous catheter as potential source of infection as soon as possible during the course of candidemia, and not replacing it with other polyurethan intravascular devices, which pose a risk for the maintenance of the fungemia despite the administration of the best antifungal therapy available.